Implementation of Sharia Accounting and Compliance with PSAK 409 in the Management of Zakat, Infaq, and Sedekah (ZIS) at Badan Amil Zakat Nasional (BAZNAS) of North Sumatra Province - Saydhina Alif; Yenni Samri Juliati Nasution; Nurwani Nurwani (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the implementation of sharia accounting and compliance with PSAK 409 in the management of zakat, infaq, and sedekah (ZIS) funds at BAZNAS, North Sumatra Province. The study used a qualitative approach with descriptive methods to gain an in-depth understanding of the practices of recognizing, measuring, presenting, and disclosing ZIS funds. Research data were obtained through interviews, observations, and review of financial statements and other supporting documents. The results of the study indicate that, in general, BAZNAS, North Sumatra Province has implemented sharia accounting and refers to the provisions of PSAK 409 in managing ZIS funds. This implementation is supported by the use of the BAZNAS Management System (SIMBA) and the implementation of periodic internal and external audits to improve transparency and accountability in fund management. However, the implementation of PSAK 409 has not been fully optimized due to obstacles in human resource competency, limited training, and inconsistent application of internal regulations. This study concludes that increasing human resource capacity and strengthening regulations are needed to support a more optimal and sustainable implementation of PSAK 409.